Co‐Occurrence of Alcohol, Drug Use, DSM‐5 Alcohol Use Disorder, and Symptoms of Drug Use Disorder on Both Sides of the U.S.–Mexico Border. (April 2015) - Borges, Guilherme; Zemore, Sarah; Orozco, Ricardo; Cherpitel, Cheryl J.; Ye, Yu; Bond, Jason; Maxwell, Jane Carlisle; Wallisch, Lynn
<x xml:space="preserve">Abstract</x> Background The U.S.–Mexico border displays elevated rates of hazardous alcohol and drug use. Whether the co‐occurrence of alcohol and drug use and disorders is also high in the border area is unknown. Methods Data are from the U.S.–Mexico Study on Alcohol and Related Conditions, a cross‐sectional survey of randomly selected respondents interviewed from 2011 to 2013. Participants included 1, 690 Mexican Americans from Texas (572 in an off‐border city and 1, 118 from 3 border cities) and 1, 293 Mexicans from Nuevo Leon and Tamaulipas (415 in an off‐border city and 878 from 3 Mexican cities bordering Texas) who reported drinking in the last 12 months. Participants were interviewed regarding the prevalence of and risk factors for: (i) co‐occurring hazardous alcohol use (5+/4+ at least monthly) and drug use (medical and illicit) and (ii) co‐occurring presence of a DSM‐5 alcohol use disorder (AUD) and 2 symptoms (hazardous use and quit/control) of drug use disorder (DUD symptoms). Results Co‐occurring hazardous alcohol and drug use was more common in the U.S. border cities (14.7%) than off‐border (7.2%), but similar for Mexican border (1.2%) and off‐border (1.4%) cities. Co‐occurrence of AUD and DUD symptoms was likewise more common at the U.S. border (6.8%) than off‐border (3.3%), as well as at the Mexican border (1.3%), compared to off‐border (0.6%), but not statistically significant for Mexico. In models adjusting for demographics, mobility factors and exposure to the U.S. culture, border residence in both countries related to a nearly twofold increase in prevalence ratios (PRs) of co‐occurring AUD and DUD symptoms (PR = 1.97, 95% CI = 1.36 to 2.85). Conclusions Increased rates of co‐occurring AUDs and DUDs suggest an added negative impact on already difficult conditions of the border population.